Whimperatives across English, Armenian and Russian Cultures - Madoyan, Lusine (Armenian Folia Anglistika, 2012)
Whimperatives express an order or a request. However, they also possess syntactic peculiarities of direct or indirect polite questions. The present article aims to investigate this type of imperative sentences and their illocutionary function in modern English, Armenian and Russian. An attempt has been made to introduce the brief summary of this unique linguistic structure and, through parallels between these languages, find out how this structure is translated and applied in various cultures.